Factors related to the absorption rate of benign thyroid nodules after image-guided microwave ablation: a 3-year follow-up. (1st January 2022) - Liu, Li-Hong; Yang, Bei-Bei; Liu, Ying; Wang, Jin-Ling; Wang, Dan-Dan; Ding, Hong-Yu; Wang, Shu-Rong
Abstract: Purpose: To assess the absorption rate and factors related to the development of benign thyroid nodules (BTNs) following image-guided microwave ablation (MWA). Materials and methods: This retrospective study reviewed nodule efficacy in patients who underwent MWA of BTNs between January 2016 and January 2018. The endpoint was a third-year follow-up. Nodules were categorized into those showing complete absorption (volumes with less than 100% volume reduction ratio (VRR) and those showing partial absorption (100% VRR)). Univariable and multivariable regression analyses were carried out to identify variables that were associated with nodule absorption rates. Results: A total of 173 BTNs (median volume= 4.23 ml; 25–75 percentiles= 2.27–9.00 ml) from 173 patients were evaluated. 49.7% (86/173) of patients had nodules that became completely absorbed. The mean VRRs of all BTNs were 18.0%, 78.7%, 89.0%, 94.5%, and 97.1% at the 1-, 6-, 12-, 24- and 36- month follow-ups. At the 3-year follow-up time point, nodule characteristics related to nodule VRR included nodule volume (adjusted odds ratio [AOR], 1.1 [95% CI: 1.0, 1.2]; p  = 0.03) and nodule margin (AOR, 5.3 [95% CI: 1.8, 16.0]; p  < 0.01). Treatment-related characteristics included energy per ml in nodular volume (AOR, 1.0 [95% CI: 1.0, 1.0]; p  < 0.01) and blockage of peripheral flow (AOR, 3.3 [95% CI: 1.3 8.3]; p  = 0.01). Conclusions: US-guided image-guided MWA results in satisfactory long-term outcomes for the patients with BTNs. Factors related to nodule absorption rate were the volume and margin of the nodule, energy per ml in nodular volume and blockage of peripheral flow.